The ethics dimension within the Responsible Research and Innovation approach: a critical analysis - Tusino, Silvia (Medicina e Morale, 2020)
Over the last decade, the expression "Responsible Research and Innovation" (RRI) has emerged as part of the vocabulary of the European science policy framework, in order to define a new approach aimed at guiding research and innovation processes towards the creation of desirable futures. This approach is related to five key objectives, ethics being one of them. The analysis of the motivations that led to RRI and of its distinctive features highlights the importance of the issues that this approach aims at tackling, especially the need of promoting the early interaction between ethical reflection, on the one hand, and techno-scientific research and innovation, on the other. However, the way the role of ethics is presented within RRI shows many limitations that could seriously undermine the potential impact of ethical reflection on research and innovation processes. These limitations are linked to: a top-down approach that's typical of RRI; the insufficient analysis of the most innovative and peculiar component of the ethical dimension - namely the critical reflection on the social impacts of research and innovation; the failure to appreciate the specificity of the contribution that normative ethics can offer. These limitations are revealed both by the analysis of the way ethics is interpreted within RRI and put in place in research institutions, and by the analysis of the theorization and of the experiences of the so-called "ethics in the laboratory". Finally, some areas in which the role of ethics and moral philosophers is crucial are identified.